MICROPROPAGATION OF GARLIC CHIVES (ALLIUM TUBEROSUM ROTTL. EX SPRANG) US ING MESOCOTYL AXIS - B. Alizadeh; S. D. Royandazagh; K. M. Khawar; S. Özcan (Journal of Animal and Plant Sciences, 2013)
Garlic chives - Allium tuberosum Rottl. ex Sprang is widely distributed from South East Asia to the Middle East. They are grown for their garlic flavored leaves and are used for culinary purposes. The plants are apomictic, which makes creation of variations and development of new varieties very difficult. The results of previous research show recalcitrant regeneration behaviour in in vitro micropropagation cultures. The study was designed to develop efficient regeneration protocols that could help in easy genetic transformation and mutation studies on MS medium containing various concentrations of TDZ-NAA, TDZ-2, 4-D and BAP-IBA using juvenile mesocotyl axis explant obtained from of one week old in vitro grown seedlings. The concentrations and combinations of different plant growth regulators in MS medium had significantly different and variable effects on bulblet regeneration. Maximum number of 7.20 shoots per explant was recorded on MS medium containing 1 mg/l BAP-2 mg/l IBA. The shoots regenerated on any regeneration medium were not difficult to root on MS medium containing 0.5 mg/l IBA. These rooted plants were easily acclimatized in the growth chamber. This study clearly shows that mesocotyl axis explants of garlic chives can be successfully cultured on BAP-IBA containing medium to regenerate axillary bulblets. To conclude, this protocol provides a successful and reliable propagation technique to regenerate garlic chive coleoptile axis excised from of one week old in vitro regenerated seedlings for the first time. This would help in advanced genetic transformation and mutation studies of the plant in future.
Keywords: Garlic chive; mesocotyl axis; in vitro; micropropagation; rooting; acclimatization